Effects of nanopores and sulfur doping on hierarchically bunched carbon fibers to protect lithium metal anode. Issue 5 (16th July 2021) - Jung, Ji In; Park, Sunwoo; Ha, Son; Cho, Se Youn; Jin, Hyoung‐Joon; Yun, Young Soo
Abstract: Studies on three‐dimensional structured carbon templates have focused on how to guide homogeneous lithium metal nucleation and growth for lithium metal anodes (LMAs). However, there is still insufficient evidence for a key factor to achieve their high electrochemical performance. Here, the effects of nanopores and sulfur doping on carbon‐based nanoporous host (CNH) electrode materials for LMAs were investigated using natural polymer‐derived CNHs. Homogeneous pore‐filling behaviors of lithium metal in the nanopores of the CNH electrode materials were first observed by ex situ scanning electron microscopy analysis, where the protective lithium metal nucleation and growth process led to significantly high Coulombic efficiency (CE) of ~99.4% and stable 600 cycles. In addition, a comparison study of CNH and sulfur‐doped CNH (S‐CNH) electrodes, which differ only in the presence or absence of sulfur, revealed that sulfur doping can cause lower electrochemical series resistance, higher CE value, and better cycling stability in a wide range of current densities and number of cycles. Moreover, S‐CNH‐based LMAs showed high electrochemical performance in full‐cell Li–S battery tests using a sulfur copolymer cathode, where a high energy density of 1370 W h kgelectrode −1 and an excellent power density of 4120 W kgelectrode −1 were obtained. Abstract : The effects of nanopores and sulfur doping on a functionalized carbon‐based nanoporous host (CNH) electrode were investigated. Sulfur doping of the CNH electrode decreased the lithium metal nucleation overpotential, increased the average Coulombic efficiency in a wide range of current densities, and afforded more stable cycling performance. In addition, in the homogeneously distributed nanopores in the sulfur‐doped CNH fibers, lithium metal nanoparticles were uniformly grown and reversibly removed by a stripping process, resulting in protective lithium metal storage.